Identification of suitable sites for rainwater and storm water harvesting through spatial analysis and smart sustainable urban water infrastructure in Lahore, Pakistan - Rumana Siddiqui; Kanwal Javid; Muhammad Irfan Ahamad (Water Science and Technology, 2023)
Sustainable and water-wise cities maintain an eco-friendly urban hydrological cycle (UHC). Regrettably, the UHC of Pakistani cities is not consistently eco-friendly. Pakistan is situated within the influential area of the world's largest monsoon weather system. Cities like Lahore face simultaneous vulnerabilities to urban flooding and water scarcity due to extreme climate change events. Therefore, Pakistan's urban areas necessitate Urban Water Infrastructural Transformation (UWIT), achievable only after identifying suitable Rainwater and Stormwater Harvesting Potential Sites (RSWHPS) in Lahore. Hence, we conducted spatial analysis to pinpoint these RSWHPS within Lahore city for 2020, utilizing the World View Water Index (WV-WI). The results indicate 85.54 km2 of available areas for rain and stormwater harvesting potential during monsoon rains in Lahore. The area with the highest potential in Lahore is Wagha town, featuring 19.96 km2 of stagnant water. Additionally, RSWHPS is classified into four categories based on potential: high, medium, low, and water bodies in Lahore. Urgent transformation is required for the identified storm and rainwater harvesting sites. Consequently, this study will serve as a snapshot for policymakers to systematically address water shortage and urban flooding, making Lahore's hydrological cycle eco-friendly and sustainable. HIGHLIGHTS The study addresses the importance of sustainable and water-wise cities in maintaining an eco-friendly urban hydrological cycle.; Recognizing the pressing need for change, the research emphasizes the requirement for urban water infrastructural transformation in Pakistan's urban areas.; The study is a valuable resource for policymakers, providing insights to systematically address water shortages and urban flooding.;